Anti-windup dead-time compensation for stable and integrative first-order dead-time processes - Torrico, Bismark Claure (2018)
This work proposes an anti-windup structure for the ltered Smith predictor (FSP) which belongs to a class of dead-time compensators (DTCs). The proposed FSP structure does not use any extra tuning parameter due to the anti-windup characteristic. In addition stability analysis is presented based on describing function method to show robustness properties of the controller. Simulation results are used to compare the obtained solution with other anti-windup DTCs and a constrained model-based predictive controller (MPC). Experimental results on a neonatal intensive care unit are presented in order to shown the usefulness of the proposed controller.